1999
DOI: 10.1046/j.1440-0952.1999.00743.x
|View full text |Cite
|
Sign up to set email alerts
|

U–Pb dating of silicic lavas, sills and syneruptive resedimented volcaniclastic deposits of the Lower Devonian Crudine Group, Hill End Trough, New South Wales

Abstract: The Hill End Trough of central‐western New South Wales was an elongate deep marine basin that existed in the Lachlan Fold Belt from the early Late Silurian to late Early Devonian. It is represented by a regionally extensive, unfossiliferous sequence of interbedded turbidites and hemipelagites of substantially silicic volcanic derivation, which passes laterally into contemporaneous shallow‐water sedimentary rocks. The Turondale and Merrions Formations of the Lower Devonian Crudine Group are two prominent volcan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 28 publications
1
21
1
Order By: Relevance
“…The final line represents a solution using proportioned biozones (based on Fordham's (1992) study, and that of Johnson et al (1991)), although only small discrepancies were observed with a version based on equal biozone lengths (Tucker et al 1998, p. 183). The time scale of Compston (2000b) is based on a time line fitted to (zircon-based ID-MS and SHRIMP) data from the Lower Palaeozoic section, reinterpreted data points from Tucker et al (1998) and one Lower Devonian point from Jagodzinski & Black (1999). Two of the data from Tucker et al (1998) are significantly different (Fig.…”
Section: Discussion Of the Evolution Of The Devonian Time Scalementioning
confidence: 99%
See 4 more Smart Citations
“…The final line represents a solution using proportioned biozones (based on Fordham's (1992) study, and that of Johnson et al (1991)), although only small discrepancies were observed with a version based on equal biozone lengths (Tucker et al 1998, p. 183). The time scale of Compston (2000b) is based on a time line fitted to (zircon-based ID-MS and SHRIMP) data from the Lower Palaeozoic section, reinterpreted data points from Tucker et al (1998) and one Lower Devonian point from Jagodzinski & Black (1999). Two of the data from Tucker et al (1998) are significantly different (Fig.…”
Section: Discussion Of the Evolution Of The Devonian Time Scalementioning
confidence: 99%
“…Middle Devonian series and stages are stippled for clarity 9 Tucker et al (1998) shown as filled error boxes, coded as in Fig. 2; data reinterpreted by Compston (2000b) are shown as open diamonds, with the corresponding code letter from (a); point L* is based on Jagodzinski & Black (1999;see Compston 2000b, table 4 for full discussion); the reinterpreted age of the Kalkberg bentonite (409.3 4-1.1 Ma la), not plotted by Compston (2000b, fig. 15), has a similar numerical age to L* but a different biostratigraphic age.…”
Section: Discussion Of the Evolution Of The Devonian Time Scalementioning
confidence: 99%
See 3 more Smart Citations